1997
DOI: 10.1097/00005768-199706000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate performance curve during incremental cycle ergometer exercise in healthy young male subjects

Abstract: In 1992 Conconi et al. (20) presented an indirect and noninvasive method for the determination of anaerobic threshold (AnT) in an incremental field test for runners. This noninvasive method for the determination of anaerobic threshold is dependent on the occurrence of a deflection of the heart rate performance curve (HRPC). The aim of our study was to evaluate the degree and direction of the deflection of the HRPC and the relationship of the heart rate threshold (HRT) to the lactate turn point in a group of 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
109
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 28 publications
16
109
1
2
Order By: Relevance
“…The nature and the risk of the experimental procedures were explained in detail and written informed consent was obtained. Within one week after the blood sampling and assessment of routine laboratory parameters, participants underwent an incremental cycle ergometer exercise 22 (ECB PRO Ergometer 850, Tunturi, Austria) starting at 35 W and increasing in increments of 10 ± 15 W every minute until voluntary exhaustion. Power output was calculated as Wakg body-weight, and in order to disentangle power output from FM, in Wakg FFM.…”
Section: Cardiovascular ®Tnessmentioning
confidence: 99%
“…The nature and the risk of the experimental procedures were explained in detail and written informed consent was obtained. Within one week after the blood sampling and assessment of routine laboratory parameters, participants underwent an incremental cycle ergometer exercise 22 (ECB PRO Ergometer 850, Tunturi, Austria) starting at 35 W and increasing in increments of 10 ± 15 W every minute until voluntary exhaustion. Power output was calculated as Wakg body-weight, and in order to disentangle power output from FM, in Wakg FFM.…”
Section: Cardiovascular ®Tnessmentioning
confidence: 99%
“…1) are represented by a third-order regression equation with two inflection points (high and low blood pressures). Previous studies 1,10) have shown that SBP during an exercise tolerance test increases slightly at a small intensity, there tends to increase rapidly when the exercise intensity rises above a certain level, but the increase is suppressed when the blood pressure is excessively elevated. This suppression of the increase is considered to be due to th e excitation of baroreceptors, which are enhanced to inhibit sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, blood pressure monitoring devices that are hardly influenced by body motions and vibrations are used in laboratoies [1][2][3][4][5][6] . However, by our results, we have shown that in an exercise tolerance test, the DPBP can be derived with a portable sphygmomanometer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anaerobic threshold (AT) determined by expired gas analysis and the lactate threshold (LT) obtained by lactate measurement are useful not only for the measurement of physical fitness in athletes but also as indices of health in middle-aged and older individuals, and of optimal exercise intensity in patients with diabetes mellitus, ischemic heart disease, or stroke [1][2][3] . However, their evaluation require an expensive expired gas analyzer and frequent blood sampling; thus, they are difficult to implement in clinical physical therapy settings.…”
Section: Introductionmentioning
confidence: 99%